Modified model for the effective thermal conductivity of metal oxide nanofluids. (2021) - Pasrija, Ritu; Gupta, Shefali
Abstract: Nanofluids, a new class of heat transfer fluids, exhibit anomalously high thermal conductivity compared to the traditional heat transfer fluids. Though many models have been proposed to provide an explanation to the underlying phenomena but there are still some issues which need to be addressed in order to gain consistency with the available experimental data. This work accounts for the factors such as interfacial nanolayer, volume fraction, temperature, static and dynamic properties of nanoparticles in formulating a modified effective thermal conductivity model. The present model shows a better agreement with the experimental data in comparison to other models for metal oxide nanofluids.